Empowering Netizenship: The Politics of Defending the Environment in an Online Petition Change.Org - Sanny Nofrima; David Efendi (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2022)
This study shows how the impact of digital democracy in the change.org online petition contributes to efforts to save environmental damage, change individual community behaviour or ecological and natural resource governance policies. To collect data, the methodology is to categorize it into environmental themes, both local, national and global, on change.org and then validate with digital activism such as discussions, spreading meme propaganda to welcome selected petitions as an effort to consolidate data by utilizing Nvivo 12 Plus to see reactions, interactions. Thematic on Twitter, national-international media websites, and other social media. Digital democracy has driven public awareness and defence of the environment in the last decade. Another finding from this research is the power of online petitions in influencing policies or policy changes resulting from interactions on social media, at least in the last ten years. However, having a significant impact requires certain prerequisites to raise awareness of digital media users and forced power holders. In some themes, the online struggle of hundreds of online petitions on environmental-themed change.org turned out to have many impacts on project cancellations, courts, criminalization by companies or law enforcement officers or delaying and cancelling certain development policies.